ANALYSIS INTELLECTUAL CAPITAL TRANSPORTATION COMPANIES IN INDONESIA STOCK EXCHANGE - Anisa Anisa; Herlambang Pudjo Santosa (Publikasi Indonesia, 2023)
This study aims to determine the effect of industry type, profitability, and leverage on Intellectual Capital in transportation companies listed on the Indonesia Stock Exchange. A total of 43 transportation companies listed on the Indonesia Stock Exchange were included in the study population from 2018 to 2021. Multiple linear regression data analysis yielded the following findings: Leverage has an effect on Intellectual Capital . Profitability has no influence on Intellectual Capital. The type of industry has an influence on Intellectual Capital